Reply on comments on ‘a lesson to learn in an Iatrogenic Perforation of Sigmoid Volvulus after Endoscopic Derotation’ - Firdaus Hayati; Nik Amin Sahid Nik Lah; Nornazirah Azizan; Nornazirah Azizan; Andee Dzulkarnaen Zakaria (2020)
Acute sigmoid volvulus is a surgical emergency, in which the initial treatment is endoscopic derotation in uncomplicated cases. Flatus tube dislodge is one of the common condition after endoscopic intervention. By performing a technique against the term of reference, management of a patient can skew towards a guarded outcome. I reply to comments on a paper concerning on iatrogenic bowel perforation after a successful endoscopic derotation of acute sigmoid volvulus.